Distinct behavioral phenotypes in ethanol-induced place preference are associated with different extinction and reinstatement but not behavioral sensitization responses - Pildervasser, João V. N.; Abrahao, Karina P.; Souza-Formigoni, Maria L. O. (Frontiers in Behavioral Neuroscience, 2014)
Conditioned place preference (CPP) is a model to study the role of drug conditioning properties. In outbred strains, individual variability may affect some behavioral measures. However, there are few studies focusing on understanding how different phenotypes of ethanol conditioned behavior may influence its extinction, reinstatement and behavioral adaptation measures. We used male Swiss Webster mice to study different phenotypes related to ethanol conditioning strength, reinstatement and behavioral sensitization. Mice went through a CPP procedure with ethanol (2.2 g/kg, i.p.). After that, one group of mice was submitted to repeated extinction sessions, while another group remained in their home cages without any drug treatment. Mice went through environmental and ethanol priming (1.0 g/kg, i.p.) reinstatement tests. Ethanol priming test reinstated the conditioned behavior only in the animals kept in the home-cage during the abstinence period. Besides, the ethanol conditioned behavior strength was positively correlated with the time required to be extinguished. In the second set of experiments, some mice went through a CPP protocol followed by behavioral sensitization (five i.p. administrations of ethanol 2.2 g/kg or saline per week, for 3 weeks) and another group of mice went through sensitization followed by CPP. No positive correlation was observed between ethanol CPP strength and the intensity of behavioral sensitization. Considering that different phenotypes observed the in CPP strength predicted the variability in other CPP measures, we developed a statistics-based method to classify mice according to CPP strength to be used in the evaluation of ethanol conditioning properties.